Hadith #3188 - Sunan Abi Dawud - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Aisha bint Abi Bakr; Falayh bin Suliaman فليح بن سليمان; Muhammad bin 'Abdullah bin 'Abbad Kufi محمد بن عبد الله بن عباد كوفي; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Salah bin 'Ajalan Hijazi صالح بن عجلان حجازي (Sunan Abi Dawud)
When Ibrahim, the son of the Prophet (ﷺ) died, he prayed over him at the place where he used to sit. Abu Dawud said: I recited to Sa’id b. Ya’qub al-Taliqani saying: Ibn al-Mubarak transmitted to you from Ya’qub b. al-Qa’qa’ on the authority of ‘Ata that the Prophet (ﷺ) prayed over his son Ibrahim when he was seventeen days old.
Grade: Da'if

Hadith #1585 - Sunan Ibn Majah - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Falayh bin Suliaman فليح بن سليمان; Salah bin 'Ajalan Hijazi صالح بن عجلان حجازي; Yonus bin Muhammad bin Muslim يونس بن محمد بن مسلم المؤدب (Sunan Ibn Majah)
Sulaiman bin Amr bin Ahwas said: “My father told me that he was present at the Farewell Pilgrimage with the Messenger of Allah. He praised and glorified Allah, and reminded and exhorted (the people). Then he said: ‘I enjoin good treatment of women, for they are prisoners with you, and you have no right to treat them otherwise, unless they commit clear indecency. If they do that, then forsake them in their beds and hit them, but without causing injury or leaving a mark. If they obey you, then
Grade: